DETECTION OF HUMAN HERPESVIRUS-8 ANTIGEN IN HIV-INFECTED PATIENTS IN EAST JAVA, INDONESIA - Oktafiani, Devi; Megasari, Ni Luh Ayu; Fitriana, Elsa; Nasronudin, Nasronudin; Lusida, Maria Inge; Soetjipto, Soetjipto (African Journal of Infectious Diseases (AJID), 2018)
Background: Co-infection of human herpesvirus-8 (HHV-8) in HIV-positive people might cause Kaposi’s sarcoma. Early detection of HHV-8 may prevent the onset of clinical manifestations. In Indonesia, detection of HHV-8 antigen in HIVpositive patients has yet to be reported. The intention of this research was to examine the presence of HHV-8 antigen in HIV-positive patients in East Java, Indonesia. Material and Methods: 103 serum samples were collected from HIV-positive patients in Surabaya and Tulungagung, East Java, Indonesia. Serums were then tested for the presence of HHV-8 antigen by using sandwich ELISA. Results: Human Herpesvirus-8 antigen was detected in 15 samples (14.5%). The presence of HHV-8 infection in HIVpositive patients did not present differently in males and females and among different age groups. Human immunodeficiency virus-positive serum samples were collected from 23 homosexual men, 25 intravenous drug users (IVDUs) and 52 heterosexuals. In the male homosexual group, HHV-8 antigen was detected in 21.7% (5/23) of the samples, while in the intravenous drug user group (IVDUs), 16% (4/25) of the samples were found to have HHV-8 antigen. Conclusion: This research found the presence of HHV-8 antigen in 14.5% of patients in East Java, Indonesia. It is recommended that patients with a positive result should receive further examination to detect any clinical manifestations related to HHV-8 infection, especially in the form of Kaposi’s sarcoma lesions, so that the illness can be appropriately managed.